PENYULUHAN LITERASI KEUANGAN RUMAH TANGGA TANI DALAM KONTEKS STRATEGI PEMISAHAN MODAL KERJA DAN PENDAPATAN KONSUMSI PADA PETANI DI KECAMATAN PANAI HULU - Praida Hansyah; Erni Wahyuni; Khairil Hanif; Lidia Sri Hardiyanti; Mulya Rafika; Mhd. Amin; Ahmad Yahdil Fata Rambe; Syaiful Zuhri Harahap (Universitas Labuhanbatu, 2026)
This community service activity aimed to improve farmers’ understanding of household financial literacy, particularly regarding the strategy of separating farming working capital from household consumption income in Panai Hulu District. The main problem faced by farming households was the low level of financial management capability and the absence of clear separation between business capital and household consumption needs. The activity involved 32 farmers and was implemented through counseling, interactive discussions, and simple financial recording assistance. The materials delivered included basic concepts of financial literacy, household financial management, strategies for separating working capital and consumption income, and farm financial planning. The results showed an improvement in participants’ understanding of the importance of structured financial management in farming households. Participants began to understand the importance of separating farming business capital from household consumption expenses and started applying simple financial recording practices in their daily economic activities. Survey results indicated that most participants gave very positive responses to the implementation of the activity and considered the materials relevant to the needs of farming communities. This community service activity provided positive implications for increasing public awareness regarding the importance of financial literacy in supporting the sustainability of farming businesses and the economic stability of farming households.Keywords: financial literacy, farming households, working capital, consumption income, counseling